Exploring the network of individuals that influence the media's inflation message in South Africa - Katrien Smuts (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2023)
The main goal of this study-and its potential to add to the policy debate-is to cast light on the network of voices that influence the narrative about inflation and monetary policy in South Africa. To that end, this paper first identifies the main individuals (journalists, domestic policy makers, and financial analysts) that influence the inflation message in the news media. Using social network analysis, graph theory, and opinion leadership techniques, I describe the relationships and identify the most prominent persons in the network. Second, I use textual analysis to compare the inflation narrative of the South African Reserve Bank with that of the financial analysts and the news media. This comparison aims to add information about what these different groups add to the narrative that is developing in the media. The paper finds some nuanced differences in the way the terms inflation and growth are used. The news has a greater focus on how inflation relates to the target. The South African Reserve Bank, in turn, focuses more on the growth outlook compared to the other two fields, while the financial analysts talk more about growth factors from outside of South Africa.
Keywords: A11; D84; D85; 330; inflation; inflation expectations; social networks; opinion leadership; South African Reserve Bank; South Africa